Recombinant Chromosomes Resulting From Parental Pericentric Inversions—Two New Cases and a Review of the Literature - Liehr, Thomas; Weise, Anja; Mrasek, Kristin; Ziegler, Monika; Padutsch, Niklas; Wilhelm, Kathleen; Al-Rikabi, Ahmed (Frontiers in Genetics, 2019)
A balanced pericentric inversion is normally without any clinical consequences for its carrier. However, there is a well-known risk of such inversions to lead to unbalanced offspring. Inversion-loop formation is the mechanism which may lead to duplication or deletion of the entire or parts of the inverted segment in the offspring. However, also partial deletion and duplication may be an effect of a parental inversion, depending on the size of the inversion and the uneven number of crossing over events, also suggested to be due to an inversion loop. Here we describe two new cases of recombinant chromosomes and provide a review of the literature of comparable cases. Interestingly, this survey confirmed the general genetic principle that gain of copy numbers are better tolerated than losses. Furthermore, there is a non-random distribution of all human chromosomes concerning their involvement in recombinant formation, which is also discussed.